The Value of Admission Serological Indicators for Predicting 28-Day Mortality in Intensive Care Patients With Acute Heart Failure: Construction and Validation of a Nomogram - Wei, Xiaoyuan; Min, Yu; Yu, Jiangchuan; Wang, Qianli; Wang, Han; Li, Shuang; Su, Li (Frontiers in Cardiovascular Medicine, 2021)
Background Acute heart failure (AHF) is a severe clinical syndrome characterized as rapid onset or worsening of symptoms of chronic heart failure (CHF). Risk stratification for AHF patients in the intensive care unit (ICU) may help clinicians predict the 28-day mortality risk in this subpopulation and further raise the quality of care. Methods We retrospectively reviewed and analyzed the demographic characteristics and serological indicators of AHF patients in the Medical Information Mart for Intensive Care III (MIMIC III, version 1.4) between Jun 2001 and Oct 2012 and our medical center between Jan 2019 and Apr 2021. The Chi-square and Fisher’s exact test were used for comparison of qualitative variables among the AHF death group and non-death group. The clinical variables were selected by using the least absolute shrinkage and selection operator (LASSO) regression. A clinical nomogram for predicting the 28-day mortality was constructed based on the multivariate Cox proportional hazard analysis and further validated by the internal and external cohorts. Results Age >65 years (Hazard ratio (HR)=2.47), high SOFA score (≥3 and ≤8, HR=2.21; ≥9 and ≤20, HR=3.29), lactic acid (Lac >2mmol/L, HR=1.40), bicarbonate (HCO3- >28 mmol/L, HR=1.59), blood urea nitrogen (BUN >21mg/dl, HR=1.75), albumin (<3.5g/dl, HR=2.02), troponin-T (TnT >0.04ng/ml, HR=4.02), and creatine kinase-MB (CKMB >5 ng/ml, HR=1.64) were the independent risk factors for predicting 28-day mortality of intensive care patients with AHF (p<0.05). The novel nomogram was developed and validated with a promising C-index of 0.814 (95% confidence interval (CI): 0.754-0.882), 0.820 (95%CI: 0.721-0.897), and 0.828 (95%CI: 0.743-0.917), respectively. Conclusions Our study provides a new insight in early predicting the risk of 28-day mortality in intensive care patients with AHF. The age, SOFA score, and serum TnT level are the leading three predictors in evaluating the short-term outcome of intensive care patients with AHF. Based on the nomogram, clinicians could better stratify the AHF patients at high risk and make adequate treatment plans.